Interactions between larvae of the threatened saproxylic beetle Osmoderma eremita and other flower chafers in Mediterranean woodlands: implications for conservation - Chiari, Stefano; Zauli, Agnese; Audisio, Paolo; Carpaneto, Giuseppe M (Insect Conservation and Diversity, 2014)
* Interactions between larvae of one of the most charismatic and threatened saproxylic beetles, Osmoderma eremita (Scopoli, 1763), and other flower chafer species (Coleoptera: Scarabaeidae) were investigated by taking samples of wood mould, i.e. loose material inside the cavity, from 151 living hollow trees in two Mediterranean woodlands during August 2010. * Multi-species occupancy models estimate low occupancy probabilities for both O. eremita (ψ ± SE = 0.36 ± 0.13) and other flower chafer species (0.42 ± 0.06), which showed similar microhabitat requirements without competing. * In cavities where larvae of both groups were present, the probability of detecting O. eremita during the sieving of 2 l of wood mould was not affected by whether larvae of other flower chafers occur in the same sample and vice versa. * Unexpectedly, larvae of O. eremita were detected with a higher probability when larvae of other flower chafers occurred in the cavity. * Model selection statistics strongly support that increasing the sampled volume of wood mould increases the probability of detecting larvae, especially for O. eremita. * Wood mould sampling resulted in a reliable method for detecting the presence of O. eremita larvae, but further studies are needed to investigate the potential damage caused by this procedure in the fragile microhabitat of tree cavities. * To preserve populations of O. eremita and other flower chafers, management actions should be focused on increasing the density of hollow trees and the volume of tree cavities by favouring the natural ageing of trees and by creating artificial habitats in living trees.
Keywords: co-occurrence; detectability; hollow trees; monitoring; occupancy; PRESENCE; Scarabaeidae; wood mould sampling